Impact of health policy implementation on service quality and patient satisfaction in primary care settings: A cross-sectional study - Anita Costanci Christine Tengker; Nancy Sylvia Bawiling (Jurnal Ilmiah Kesehatan Sandi Husada, 2026)
Introduction: Effective implementation of health policy at the primary care level remains uneven, often limiting its impact on service quality and patient satisfaction. This study aimed to examine the effect of health policy implementation on service quality and patient satisfaction in primary care settings. Research Methodology: An analytical cross-sectional study was conducted among 145 patients attending primary healthcare facilities. Participants were selected using systematic random sampling. Health policy implementation was assessed across three domains: policy adherence, resource availability, and provider compliance. Service quality was measured using a modified SERVQUAL instrument, while patient satisfaction was assessed using a standardized Likert-scale questionnaire. Data were analyzed using descriptive statistics, bivariate analysis, and multiple linear regression. Statistical significance was set at p < 0.05. Results: Health policy implementation showed a significant positive association with service quality (β = 0.52; 95% CI: 0.34–0.70; p < 0.001) and patient satisfaction (β = 0.47; 95% CI: 0.29–0.65; p < 0.001). Multivariate analysis revealed that policy adherence was the strongest predictor of service quality (β = 0.31; 95% CI: 0.18–0.44; p < 0.001) and patient satisfaction (β = 0.29; 95% CI: 0.16–0.42; p < 0.001), followed by resource availability and provider compliance, all of which remained statistically significant. Conclusion: The findings indicate that strengthening health policy implementation, particularly adherence and resource support, is essential to improve service quality and patient satisfaction. Policy efforts should prioritize implementation fidelity, workforce capacity, and equitable resource allocation to enhance patient-centered outcomes in primary healthcare.